Estudo e elaboração da matriz de reconhecimento de perigos e riscos em uma fábrica de papel no município de Belém/PA - OLIVEIRA, Dayse Kellen Ferreira de (2022)
Organizations have been looking for new solutions in the face of the possibility of large amounts of accidents and incidents. Thus, they have been looking for alternatives for anticipation, mapping, evaluation and proposals for dealing with each situation found in their work environments. New systems for managing risks and deviations found in places where work activities are carried out have been increasing, demonstrating that these resources result in increased benefits in terms of knowledge of environmental risks in activities carried out by workers. In this context, the risk mapping and mitigation method proposed in this work contributes to improving working conditions and reducing the number of occurrences that can generate accidents. The implementation of this tool has as its main objective the improvement of its production process and preventive action regarding the anticipation of risk recognition and mitigation actions to prevent situations highlighted in the research with high potential from generating new occurrences. It should be noted that with structured risk management, the elaboration of the preliminary risk analysis (APR) can be excluded, and with that, production gains time in the execution of its activities. In addition, with the elaboration of the Hazards and Risk Recognition Matrix, the company will have its hazards and risks mapped and will optimize its processes due to the reduction of wasted time, as the average time was forty-eight hours for preparation and release of an APR, for the beginning of the activities.